Water-based zinc battery, electrode / electrolyte interface and preparation method

Through the cross-linking technology of hydrophilic positive electrode and hydrogel electrolyte, the electrode/electrolyte interface of the water-based zinc battery is constructed, which solves the problems of electrode performance limitation and binder swelling, and improves the stability and circulation performance of the battery.

CN119581700APending Publication Date: 2025-03-07ZHEJIANG WEILAN CREATION TECH GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411796271.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In actual applications, water-based zinc batteries have problems such as material stability, electrode wetting and oxygen evolution reaction at high voltage, resulting in limited electrode performance. The commonly used positive electrode binder swells and detaches in the aqueous electrolyte, and cannot be directly applied to water-based zinc batteries.

Method used

By crosslinking the hydrophilic cathode and hydrogel electrolytes with each other under the action of the electrolyte, an electrode/electrolyte interface is constructed, and the quasi-solid electrolyte is used to form a quasi-solid electrolyte, which enhances the mechanical properties and ion transport capabilities of the electrodes.

Benefits of technology

Effectively prevent the peeling and dissolution of the binder, enhance the stability of the positive electrode, inhibit the growth of the dendrites of the zinc negative electrode, and improve the circulation and charge and discharge performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581700A_ABST
    Figure CN119581700A_ABST
Patent Text Reader

Abstract

The invention relates to a new energy and energy storage technology, and discloses a water-based zinc battery, an electrode / electrolyte interface and a preparation method, the water-based zinc battery comprises the electrode / electrolyte interface, and the preparation method of the electrode / electrolyte interface is as follows: a hydrophilic positive electrode and a hydrogel electrolyte are mutually crosslinked under the action of an electrolyte to obtain the electrode / electrolyte interface. A quasi-solid interface is formed after the hydrophilic positive electrode and the hydrogel electrolyte are cross-linked, so that falling and dissolving of a binder can be effectively prevented, and the stability of the positive electrode is enhanced. And meanwhile, dendritic crystal growth of the zinc negative electrode is inhibited by virtue of the mechanical strength of the gel, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to new energy and energy storage technology, and in particular to a water-based zinc battery, an electrode / electrolyte interface and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been the most mainstream storage technology in the energy industry due to their high energy density and long cycle life. However, lithium-ion batteries still have many defects, such as being flammable and explosive, expensive, and polluting the environment. Therefore, it is urgent to develop a secondary battery system with high energy density, good safety, and low production cost.

[0003] Water-based zinc battery is a rechargeable secondary battery with large capacity, long life, and is safer without the risk of explosion or fire. It has unique advantages in safety, cost, and certain large-scale energy storage scenarios, and has good promotion and application value.

[0004] However, its practical application is still limited by many factors. For example, in the positive electrode, material stability, electrode wettability and potential oxygen evolution reaction at high voltage affect the electrode performance.

[0005] Commonly used positive electrode binders are hydrophobic and require the use of expensive and toxic organic solvents during the processing stage, which limits the adhesiveness of the binder, hinders the wetting of the electrolyte on the electrode and the ion transport, and increases the production cost of the battery. Although the use of easy-to-process hydrophilic binders can reduce costs and facilitate the transport of ions in the electrode, hydrophilic binders will swell, detach and disperse in aqueous electrolytes and cannot be directly used in water-based zinc batteries.

[0006] Therefore, how to improve the actual performance of water-based zinc batteries so that they can better serve as a secondary battery system with high energy density, good safety and low production cost is an urgent problem to be solved in the industry. Summary of the invention

[0007] The present invention aims at the problems existing in the actual use of water-based zinc batteries in the prior art and provides a water-based zinc battery, an electrode / electrolyte interface and a preparation method.

[0008] In order to solve the above technical problems, the present invention is solved by the following technical solutions: A method for preparing an electrode / electrolyte interface comprises cross-linking a hydrophilic positive electrode and a hydrogel electrolyte under the action of an electrolyte to obtain an electrode / electrolyte interface.

[0009] As a wet and soft polymer material, hydrogel has abundant hydrophilic polymer chains and can cross-link with salt solution to form a quasi-solid electrolyte with large specific surface area and excellent ion transfer ability. With the help of the cross-linking characteristics of hydrogel, a hydrophilic electrode / electrolyte quasi-solid self-reinforced interface is constructed to reduce the negative effects of water molecules, avoid the shedding and dissolution of binders, improve the mechanical properties of electrodes, and reduce mass transfer resistance.

[0010] At the same time, with the help of the mechanical strength of the hydrogel itself, the dendrite growth of the zinc negative electrode can be physically inhibited, the electrode stability can be enhanced, the battery short circuit can be avoided, and then the charge and discharge performance of the electrode can be improved.

[0011] As a preference, the method specifically comprises the following steps: Step S1, preparing a hydrophilic positive electrode, a hydrogel electrolyte and an electrolyte; Step S2: drip 0.5 to 100 μL of electrolyte between the hydrophilic positive electrode and the hydrogel electrolyte.

[0012] Preferably, the amount of electrolyte added is 5 to 20 μL.

[0013] Preferably, step S1 includes preparing a hydrophilic positive electrode, specifically comprising the following steps: Step S11, preparing the positive electrode main material: mixing the positive electrode conductive agent and the active material and ball milling them to obtain a main material mixture after ball milling; Step S12, preparing positive electrode slurry: dissolving a hydrophilic binder in deionized water to obtain a binder solution, pouring the ball-milled main material mixture into the binder solution and stirring, and then performing ultrasonic dispersion to form a uniform positive electrode slurry; Step S13, coating: coating the positive electrode slurry evenly on the current collector and heating it on a hot plate, and then heating and drying it in a vacuum environment to obtain a hydrophilic positive electrode.

[0014] Preferably, in step S11, the mass ratio of the positive electrode conductive agent to the active material is 7:2, the positive electrode conductive agent includes conductive graphite, conductive carbon black, carbon nanotubes or graphene; the active material includes manganese-based compounds, vanadium-based compounds, Prussian blue analogs or organic compounds.

[0015] Preferably, the positive electrode conductive agent is Ketjen black or acetylene black; and the active material is α-type manganese dioxide with a tunnel structure.

[0016] Preferably, the hydrophilic binder in step S12 is a polymer material containing hydrophilic groups such as hydroxyl and carboxyl, and the concentration is 0.05wt%-2wt%, and more preferably 0.25wt%-1wt%.

[0017] Preferably, the hydrophilic binder is sodium alginate, sodium carboxymethyl cellulose, carboxyethyl cellulose, polyacrylic acid, polyethylene glycol, polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide or styrene-butadiene rubber.

[0018] Preferably, the current collector in step S13 is a metal titanium foil, titanium mesh, titanium sheet, titanium plate, stainless steel sheet or carbon cloth with a thickness of 0.05-0.3 mm.

[0019] Preferably, step S1 includes preparing a hydrogel electrolyte, comprising the following steps: Step S21, precursor preparation: heat and stir polyvinyl alcohol and sodium alginate in deionized water until the powder is completely dissolved to obtain a precursor solution; Step S22, cross-linking molding: pouring the precursor solution into a mold, placing it in a refrigerator for freezing molding, and obtaining an initial hydrogel after eliminating ice crystals at room temperature; Step S23, immersing the initial hydrogel in an electrolyte to form a hydrogel electrolyte cross-linked with polyvinyl alcohol and sodium alginate.

[0020] Preferably, in step S21, the mass ratio of polyvinyl alcohol to sodium alginate is 2-10:1.

[0021] Preferably, the molecular weight of polyvinyl alcohol is 165000-225000, and the concentration is 5wt% to 20wt%.

[0022] Preferably, in step S21, the heating temperature of polyvinyl alcohol and sodium alginate in deionized water is 70-95°C.

[0023] Preferably, the electrolyte comprises a neutral or weakly acidic zinc salt solution with a concentration of 0.5-3.5 mol L-1.

[0024] Preferably, the electrolyte includes zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate or zinc perchlorate solution.

[0025] An electrode / electrolyte interface is prepared by using the aforementioned method for preparing an electrode / electrolyte interface.

[0026] A water-based zinc battery comprises the aforementioned electrode / electrolyte interface.

[0027] Preferably, the water-based zinc battery is an aqueous zinc ion battery or a zinc-to-zinc half-cell.

[0028] A method for preparing a water-based zinc battery comprises the following steps: Step 1: Preparation of zinc electrode: Use metal zinc foil, polish to remove the oxide layer, wash with ethanol and then vacuum dry to obtain a zinc electrode sheet; Step 2: Preparation of electrolyte: dissolving neutral or weakly acidic zinc salt in deionized water and using manganese sulfate as an additive to prepare electrolyte; Step 2: Preparation of the battery: The hydrophilic positive electrode and the zinc negative electrode are separated by a hydrogel electrolyte, and the electrolyte is dripped on both sides of the hydrogel, and then the button battery shell is encapsulated to prepare a water-based zinc battery.

[0029] Preferably, the concentration of manganese sulfate is 0.2 mol L -1 , the molar ratio of neutral or weakly acidic zinc salt to manganese sulfate is 0.5-3.5:0.2.

[0030] The present invention has significant technical effects due to the adoption of the above technical solution: The present invention forms a quasi-solid interface by cross-linking the hydrophilic positive electrode and the hydrogel electrolyte, which can effectively prevent the binder from falling off and dissolving, and enhance the stability of the positive electrode. At the same time, with the help of the mechanical strength of the gel itself, the dendrite growth of the zinc negative electrode is inhibited, and the cycle performance of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an optical photograph of the hydrogel electrolyte PVA-Alg-2M in Example 4.

[0032] Figure 2 It is the uniaxial tensile strength of the hydrogel electrolytes PVA-Alg-2M and PVA-Alg-3M in Example 4.

[0033] Figure 3 The ionic conductivity and water content of the hydrogel electrolytes PVA-Alg-2M and PVA-Alg-3M in Example 4.

[0034] Figure 4 These are optical photographs of the hydrophilic positive electrode of Example 1 used under different conditions, wherein the hydrogel electrolyte is PVA-Alg-2M.

[0035] Figure 5 This is a SEM cross-sectional image of the contact interface between the hydrogel electrolyte PVA-Alg-2M and the hydrophilic positive electrode in Example 4.

[0036] Figure 6 (a) Cycle performance, (b) Voltage curve, (c) SEM image of the positive electrode after cycling, and (d) SEM image of the zinc negative electrode after cycling of the aqueous zinc ion battery in Example 5.

[0037] Figure 7 (a) Cycle performance, (b) Voltage curve, (c) SEM image of the positive electrode after cycling, and (d) SEM image of the zinc negative electrode after cycling of the aqueous zinc ion battery in Example 6.

[0038] Figure 8(a) Cycle performance and (b) voltage curve of the aqueous zinc ion battery in Example 7.

[0039] Fig. 9 (a) Cycle performance and (b) voltage curve of the aqueous zinc ion battery in Example 8.

[0040] Fig.10 (a) Cycle performance and (b) voltage curve of the aqueous zinc ion battery in Example 9.

[0041] Fig.11 The cycling performance of the zinc-to-zinc half-cells described in Examples 10 and 11. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0043] Example 1 This example provides a method for preparing a sodium alginate hydrophilic positive electrode.

[0044] (1) Manganese dioxide and Ketjen black were mixed and ball-milled in a mass ratio of 7:2. The ball-milling speed was set to 400 r / min, with one circle of 10 min and a rest of 5 min, and this process was repeated for 18 cycles.

[0045] (2) Dissolve an appropriate amount of sodium alginate in 20 mL of deionized water to prepare a solution with a concentration of 0.5 wt%. Pour the ball-milled manganese dioxide mixture into the solution and stir for 2 h, followed by ultrasonic dispersion for 20 min to form a uniform electrode slurry.

[0046] (3) Use a scraper to evenly coat the slurry on a 0.1 mm thick titanium mesh, and then lay the titanium mesh flat on a hot plate and heat it at 90 °C to evaporate it. After the solvent evaporates to the point where the slurry does not flow significantly, place the electrode in a vacuum drying oven at 80 °C and dry it for 36 h.

[0047] Example 2 This example provides a method for preparing a sodium carboxymethyl cellulose hydrophilic positive electrode.

[0048] Steps (1) to (3) in Example 1 were performed, wherein sodium alginate was replaced by sodium carboxymethyl cellulose.

[0049] Example 3 Preparation of Comparative Example Polyvinylidene fluoride Positive Electrode Steps (1) to (3) in Example 1 were performed, wherein sodium alginate was replaced by polyvinylidene fluoride, and deionized water was replaced by N-methylpyrrolidone.

[0050] Example 4 This example provides the preparation of a hydrogel electrolyte and related performance performance.

[0051] (1) Polyvinyl alcohol and sodium alginate were mixed at a mass ratio of 5:1 and heated and stirred. The concentration of polyvinyl alcohol was 10 wt %. Specifically, 0.2 g of sodium alginate was added to 8.8 g of deionized water. After the powder was fully dissolved, 1 g of polyvinyl alcohol was added to the solution. The mixture was then heated and stirred at 90 °C for 2 h to prepare a precursor solution.

[0052] (2) The precursor solution was injected into the homemade mold and separated by a spacer. The mold was stored in a refrigerator at -30 °C for 12 h and then placed in an air environment for 6 h.

[0053] (3) The initial gel was immersed in 2 mol L-1 and 3 mol L-1 zinc sulfate solutions for at least 3 days to reach equilibrium, and a polyvinyl alcohol and sodium alginate cross-linked hydrogel electrolyte was prepared. The corresponding hydrogel electrolytes were named PVA-Alg-2M and PVA-Alg-3M, respectively. Figure 1 shown.

[0054] The prepared hydrogel electrolyte samples have high mechanical strength, e.g. Figure 2 As shown, the tensile fracture strengths of PVA-Alg-3 M and PVA-Alg-2M samples are greater than 5 MPa and 2 MPa, respectively.

[0055] like Figure 3 As shown, PVA-Alg-2M exhibits higher ionic conductivity and water content.

[0056] The hydrophilic alginate positive electrode was placed in deionized water and 2 mol L-1 zinc sulfate solution, respectively. After soaking in deionized water for a few minutes, the powder on the hydrophilic positive electrode began to fall off and flocs appeared in the water, indicating that the sodium alginate diffused into the water after excessive swelling, resulting in damage to the electrode structure. In the zinc sulfate solution, due to the presence of zinc ions, the structure of the sodium alginate is more compact than in deionized water, but it still cannot prevent the active material from falling off.

[0057] like Figure 4 As shown in the figure, when the hydrogel electrolyte and the hydrophilic cathode were in contact for a period of time before being immersed in the electrolyte, no black powder was observed to diffuse into the solution after immersion for more than 1 h. This shows that the use of the hydrogel electrolyte alleviates the problem caused by the swelling of the hydrophilic binder and can effectively protect the electrode structure.

[0058] In addition, if Figure 5 As shown, close cross-linking is formed between the hydrogel electrolyte and the hydrophilic cathode, and no obvious boundary is observed.

[0059] Example 5 This example shows the actual performance of using sodium alginate hydrophilic cathode directly to prepare aqueous zinc ion batteries (RAZIBs).

[0060] (1) The sodium alginate hydrophilic positive electrode prepared in Example 1 and the polished zinc sheet were cut into discs with a diameter of 12 mm, and the glass fiber separator was cut into discs with a diameter of 16 mm. The electrolyte was a mixed solution of 2 mol L-1 zinc sulfate and 0.2 mol L-1 manganese sulfate. The aqueous zinc-manganese secondary battery was assembled in the following order: negative electrode shell, spring sheet, gasket, zinc negative electrode, glass fiber separator, electrolyte addition, positive electrode, and positive electrode shell. The electrolyte addition amount was 200 μL.

[0061] (2) The battery obtained in (1) was subjected to constant current charge and discharge tests at a current of 0.3 C (1 C = 308 mA g-1). The charge cut-off voltage was 1.9 V and the discharge cut-off voltage was 0.8 V.

[0062] like Figure 6 As shown in (a) and (b), using a hydrophilic positive electrode directly in an aqueous electrolyte will result in an unstable battery charging voltage curve with large fluctuations, and the charging capacity will significantly exceed the theoretical capacity. This is because the electrode is damaged after wetting, resulting in the shedding of active materials, such as Figure 6 (c) This part of the capacity obtained has poor reversibility and cannot be regarded as part of the battery's available capacity.

[0063] Figure 6 As shown in (d), the zinc anode using glass fiber and aqueous electrolyte suffered severe surface damage after just ten cycles, with large pieces of zinc metal deposited unevenly on the electrode surface.

[0064] Example 6 This example shows the actual performance of combining a sodium alginate hydrophilic cathode with a PVA-Alg-2M hydrogel electrolyte for preparing RAZIBs, and compares it with Example 5 to illustrate the effect of using a hydrogel electrolyte and a hydrophilic cathode to construct a quasi-solid interface on battery performance.

[0065] (1) The sodium alginate hydrophilic positive electrode prepared in Example 1 and the polished zinc sheet were cut into discs with a diameter of 12 mm, and the PVA-Alg-2M hydrogel electrolyte was cut into discs with a diameter of 16 mm. The electrolyte was a mixed solution of 2 mol L-1 zinc sulfate and 0.2 mol L-1 manganese sulfate. The aqueous zinc-manganese secondary battery was assembled in the following order: negative electrode shell, spring, gasket, zinc negative electrode, PVA-Alg-2M, electrolyte addition, positive electrode, and positive electrode shell. The amount of electrolyte added was 10 μL.

[0066] (2) The battery obtained in (1) was subjected to constant current charge and discharge tests at a current of 0.3 C (1 C = 308 mA g-1). The charge cut-off voltage was 1.9 V and the discharge cut-off voltage was 0.8 V.

[0067] The initial discharge capacity of the battery using sodium alginate hydrophilic cathode and PVA-Alg-2M is 276.5 mAh g-1, and the capacity retention rate is 73.6% after 300 cycles. Figure 7 (a) shown.

[0068] Compared with the direct use of hydrophilic cathode, the cross-linking of PVA-Alg hydrogel electrolyte with the hydrophilic cathode makes the battery have a more stable charge and discharge curve and a more obvious voltage platform, such as Figure 7 (b) shown.

[0069] The combination of hydrophilic cathode and hydrogel electrolyte can form a quasi-solid self-reinforced interface, which effectively prevents the dissolution and shedding of the binder. Figure 7 As shown in (c), the stability and cycle performance of the positive electrode are enhanced, which is consistent with the optical observation results after the positive electrode is immersed in Example 4.

[0070] The zinc negative electrode using PVA-Alg-2.0M hydrogel electrolyte can still maintain a smooth surface morphology after 300 charge and discharge cycles. There is no obvious damage or protrusion on the zinc metal surface. The deposited metal zinc evenly fills the pits produced by zinc dissolution in a flat state. Figure 7 (d) shown.

[0071] This indicates that the electrochemical deposition of Zn under the protection of the hydrogel electrolyte has good uniformity and reversibility.

[0072] Example 7 This example shows the actual performance of combining a sodium alginate hydrophilic cathode with a PVA-Alg-3M hydrogel electrolyte for preparing RAZIBs, which together with Example 6 illustrates the effect of hydrogel electrolytes prepared using electrolytes of different concentrations on battery performance.

[0073] (1) The sodium alginate hydrophilic positive electrode prepared in Example 1 and the polished zinc sheet were cut into discs with a diameter of 12 mm, and the PVA-Alg-3M hydrogel electrolyte was cut into discs with a diameter of 16 mm. The electrolyte was a mixed solution of 3 mol L-1 zinc sulfate and 0.2 mol L-1 manganese sulfate. The aqueous zinc-manganese secondary battery was assembled in the following order: negative electrode shell, spring sheet, gasket, zinc negative electrode, PVA-Alg-3M, electrolyte addition, positive electrode, and positive electrode shell. The amount of electrolyte added was 10 μL.

[0074] (2) The battery obtained in (1) was subjected to constant current charge and discharge tests at a current of 0.3 C (1 C = 308 mA g-1). The charge cut-off voltage was 1.9 V and the discharge cut-off voltage was 0.8 V.

[0075] The initial discharge capacity of the battery using sodium alginate hydrophilic cathode and PVA-Alg-3M is 287.8 mAh g-1, and the capacity retention rate is 54.3% after 300 cycles. Figure 8 Compared with PVA-Alg-2M, the battery using PVA-Alg-3M has a higher initial discharge capacity, but a lower capacity retention rate.

[0076] Example 8 This example shows the actual performance of the combination of sodium carboxymethyl cellulose hydrophilic positive electrode and PVA-Alg-2M hydrogel electrolyte for preparing RAZIBs, which together with Example 6 illustrates the effect of using positive electrodes with different hydrophilic binders on battery performance.

[0077] (1) The sodium carboxymethyl cellulose hydrophilic positive electrode prepared in Example 2 and the polished zinc sheet were cut into discs with a diameter of 12 mm, and the PVA-Alg-2M hydrogel electrolyte was cut into discs with a diameter of 16 mm. The electrolyte was a mixed solution of 2 mol L-1 zinc sulfate and 0.2 mol L-1 manganese sulfate. The aqueous zinc-manganese secondary battery was assembled in the following order: negative electrode shell, spring, gasket, zinc negative electrode, PVA-Alg-2M, electrolyte addition, positive electrode, and positive electrode shell. The amount of electrolyte added was 10 μL.

[0078] (2) The battery obtained in (1) was subjected to constant current charge and discharge tests at a current of 0.3 C (1 C = 308 mA g-1). The charge cut-off voltage was 1.9 V and the discharge cut-off voltage was 0.8 V.

[0079] The initial discharge capacity of the battery using sodium carboxymethyl cellulose hydrophilic cathode and PVA-Alg-2M is 279.9 mAhg-1, and the capacity retention rate is 40% after 300 cycles. Fig. 9 Compared with sodium alginate, the battery using sodium carboxymethyl cellulose hydrophilic cathode has a higher initial discharge capacity, but the capacity retention rate is lower.

[0080] Example 9 This example shows the actual performance of the comparative example of the combination of polyvinylidene fluoride positive electrode and hydrogel electrolyte for preparing RAZIBs, and compares it with Example 6 and Example 8 to illustrate the influence of the positive electrode using hydrophilic binder and hydrophobic binder on the battery performance.

[0081] (1) The polyvinylidene fluoride positive electrode prepared in Example 3 and the polished zinc sheet were cut into discs with a diameter of 12 mm, and the PVA-Alg-2M hydrogel electrolyte was cut into discs with a diameter of 16 mm. The electrolyte was a mixed solution of 2 mol L-1 zinc sulfate and 0.2 mol L-1 manganese sulfate. The aqueous zinc-manganese secondary battery was assembled in the following order: negative electrode shell, spring, gasket, zinc negative electrode, PVA-Alg-2M, electrolyte addition, positive electrode, and positive electrode shell. The amount of electrolyte added was 10 μL.

[0082] (2) The battery obtained in (1) was subjected to constant current charge and discharge tests at a current of 0.3 C (1 C = 308 mA g-1). The charge cut-off voltage was 1.9 V and the discharge cut-off voltage was 0.8 V.

[0083] The initial discharge capacity of the battery using polyvinylidene fluoride positive electrode and PVA-Alg-2M is 234.1 mAh g-1, and the capacity retention rate is 28% after 300 cycles. Fig.10 (a) shown.

[0084] When polyvinylidene fluoride is used as the positive electrode binder, the battery discharge voltage curve shows a sloping trend and there is no obvious platform voltage. This is because the electrode reaction is limited to the positive electrode surface, and the internally consumed electrolyte cannot be replenished in time, resulting in rapid capacity decay. Fig.10 (b) Compared with batteries using hydrophobic binders, batteries using hydrophilic cathodes have better charge-discharge and cycle performance. This advantage is attributed to the quasi-solid interface formed by cross-linking between the hydrophilic cathode and hydrogel electrolyte, which ensures smooth ion transport and maintains a complete electrode structure.

[0085] Example 10 This example shows the actual performance of PVA-Alg-2M hydrogel electrolyte in preparing zinc-to-zinc half-cells.

[0086] (1) Cut the polished zinc sheet into discs with a diameter of 12 mm, and cut the PVA-Alg-2M hydrogel electrolyte prepared in Example 4 into discs with a diameter of 16 mm. Assemble the zinc-zinc half-cell in the following order: negative electrode shell, spring, gasket, zinc sheet, PVA-Alg-2M gel electrolyte, dripping electrolyte, zinc sheet, and positive electrode shell. The amount of electrolyte dripped was 10 μL on each side.

[0087] (2) The half-cell obtained in (1) was subjected to constant current charge and discharge tests with a current of 1 mA cm-2 and a charge and discharge time of 1 h. That is, the maximum capacity that can be achieved by charge and discharge is 1 mAh cm-2. The charge cut-off voltage is 0.5 V and the discharge cut-off voltage is -1 V. When the charge voltage reaches 0.5 V, the charge process will be terminated prematurely, and the discharge process is the same.

[0088] Embodiment 11 This example shows the actual performance of a comparative glass fiber separator used to prepare a zinc-on-zinc half-cell, and compares it with Example 10 to illustrate the effect of the hydrogel electrolyte on the performance of the zinc-on-zinc half-cell.

[0089] The steps (1) and (2) in Example 10 were performed, wherein the PVA-Alg-2M hydrogel electrolyte was replaced with a glass fiber separator.

[0090] The PVA-Alg-2M hydrogel has high mechanical strength and can mechanically inhibit the growth of dendrites through physical contact, thereby promoting uniform deposition of zinc ions and avoiding short circuits. The zinc-to-zinc half-cell using the hydrogel electrolyte did not short-circuit during repeated deposition / stripping cycles for more than 800 h, while the half-cell using the traditional glass fiber separator would fail quickly, such as Fig.11 shown.

[0091] It is easy to understand that those skilled in the art can combine, split, reorganize, etc. the embodiments of the present application to obtain other embodiments based on one or several embodiments provided in the present application, and these embodiments do not exceed the protection scope of the present application.

[0092] In conclusion, the above is only a preferred embodiment of the present invention, and all equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the patent of the present invention.

Claims

1. A method for preparing an electrode / electrolyte interface, characterized in that: The hydrophilic positive electrode and the hydrogel electrolyte are cross-linked with each other under the action of the electrolyte to obtain an electrode / electrolyte interface.

2. The method for preparing an electrode / electrolyte interface according to claim 1, characterized in that: The specific steps include: Step S1, preparing a hydrophilic positive electrode, a hydrogel electrolyte and an electrolyte; Step S2: drip 0.5 to 100 μL of electrolyte between the hydrophilic positive electrode and the hydrogel electrolyte.

3. The method for preparing an electrode / electrolyte interface according to claim 2, characterized in that: The amount of electrolyte added was 5 to 20 μL.

4. The method for preparing an electrode / electrolyte interface according to claim 2, characterized in that: Step S1 includes the preparation of a hydrophilic positive electrode, specifically comprising the following steps: Step S11, preparing the positive electrode main material: mixing the positive electrode conductive agent and the active material and ball milling them to obtain a main material mixture after ball milling; Step S12, preparing positive electrode slurry: dissolving a hydrophilic binder in deionized water to obtain a binder solution, pouring the ball-milled main material mixture into the binder solution and stirring, and then performing ultrasonic dispersion to form a uniform positive electrode slurry; Step S13, coating: coating the positive electrode slurry evenly on the current collector and heating it on a hot plate, and then heating and drying it in a vacuum environment to obtain a hydrophilic positive electrode.

5. The method for preparing an electrode / electrolyte interface according to claim 4, characterized in that: In step S11, the mass ratio of the positive electrode conductive agent to the active material is 7:2, the positive electrode conductive agent includes conductive graphite, conductive carbon black, carbon nanotubes or graphene; the active material includes manganese-based compounds, vanadium-based compounds, Prussian blue analogs or organic compounds.

6. The method for preparing an electrode / electrolyte interface according to claim 5, characterized in that: The positive electrode conductive agent is Ketjen black or acetylene black; the active material is α-type manganese dioxide with a tunnel structure.

7. The method for preparing an electrode / electrolyte interface according to claim 4, characterized in that: In step S12, the hydrophilic binder is a polymer material containing hydrophilic groups such as hydroxyl groups and carboxyl groups, and the concentration is 0.05wt%-2wt%.

8. The method for preparing an electrode / electrolyte interface according to claim 7, characterized in that: The hydrophilic binder is sodium alginate, sodium carboxymethyl cellulose, carboxyethyl cellulose, polyacrylic acid, polyethylene glycol, polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide or styrene-butadiene rubber.

9. The method for preparing an electrode / electrolyte interface according to claim 4, characterized in that: In step S13, the current collector is a 0.05-0.3 mm thick metal titanium foil, titanium mesh, titanium sheet, titanium plate, stainless steel sheet or carbon cloth.

10. The method for preparing an electrode / electrolyte interface according to claim 2, characterized in that: Step S1 includes the preparation of a hydrogel electrolyte, comprising the following steps: Step S21, precursor preparation: heat and stir polyvinyl alcohol and sodium alginate in deionized water until the powder is completely dissolved to obtain a precursor solution; Step S22, cross-linking molding: pouring the precursor solution into a mold, placing it in a refrigerator for freezing molding, and obtaining an initial hydrogel after eliminating ice crystals at room temperature; Step S23, immersing the initial hydrogel in an electrolyte to form a hydrogel electrolyte cross-linked with polyvinyl alcohol and sodium alginate.

11. The method for preparing an electrode / electrolyte interface according to claim 10, characterized in that: In step S21, the mass ratio of polyvinyl alcohol to sodium alginate is 2-10:

1.

12. A method for preparing an electrode / electrolyte interface according to claim 10 or 11, characterized in that: The molecular weight of the polyvinyl alcohol is 165,000 to 225,000, and the concentration is 5 wt % to 20 wt %.

13. The method for preparing an electrode / electrolyte interface according to claim 10, characterized in that: In step S21, the heating temperature of polyvinyl alcohol and sodium alginate in deionized water is 70-95°C.

14. A method for preparing an electrode / electrolyte interface according to claim 1, 2 or 10, characterized in that: The electrolyte includes a neutral or weakly acidic zinc salt solution with a concentration of 0.5-3.5 mol L-1.

15. A method for preparing an electrode / electrolyte interface according to claim 14, characterized in that: The electrolyte includes zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate or zinc perchlorate solution.

16. An electrode / electrolyte interface, characterized in that: It is prepared by the method for preparing an electrode / electrolyte interface according to any one of claims 1 to 15.

17. A water-based zinc battery, characterized in that: Comprising an electrode / electrolyte interface as described in claim 16.

18. A water-based zinc battery according to claim 17, characterized in that: The water-based zinc battery is an aqueous zinc ion battery or a zinc-to-zinc half-cell.

19. A method for preparing the water-based zinc battery according to claim 17 or 18, characterized in that It includes the following steps: Step 1: Preparation of zinc electrode: Use metal zinc foil, polish to remove the oxide layer, wash with ethanol and then vacuum dry to obtain a zinc electrode sheet; Step 2: Preparation of electrolyte: dissolving neutral or weakly acidic zinc salt in deionized water and using manganese sulfate as an additive to prepare electrolyte; Step 2: Preparation of the battery: The hydrophilic positive electrode and the zinc negative electrode are separated by a hydrogel electrolyte, and the electrolyte is dripped on both sides of the hydrogel respectively, and then the button battery shell is encapsulated to prepare a water-based zinc battery.

20. The method according to claim 19, characterized in that The concentration of manganese sulfate is 0.2 mol L-1, and the molar ratio of neutral or weakly acidic zinc salt to manganese sulfate is 0.5-3.5:0.2.

Citation Information

Cited By

  • Hydrogel electrolyte, aqueous zinc-based battery and preparation method of aqueous zinc-based battery

    CN120767443A